On a search for a Regulation Reduction Act (RRA) - Béatrice Dumont (EconPol Forum, 2024)
Ambitious regulatory standards can stimulate innovation and competitiveness. Complexity of regulation is perceived as a burden for firms. Debate on regulation versus competitiveness is inconclusive. Need for metrics to assess the notion of complex/sophisticated regulation. Smart regulation based on systematic ex post evaluation with review clauses might be a path to explore.
Keywords: 330